Association between adiponectin and newly diagnosed type 2 diabetes in population with the clustering of obesity, dyslipidaemia and hypertension: a cross-sectional study. Issue 2 (24th February 2023) - Hong, Xiaosi; Zhang, Xiaoyun; You, Lili; Li, Feng; Lian, Hong; Wang, Jiahuan; Mao, Na; Ren, Meng; Li, Yan; Wang, Chuan; Sun, Kan
Abstract : Objectives: Adiponectin is closely related to glucose metabolism and traditional diabetes risk factors (obesity, hypertension and dyslipidaemia). We aimed to explore the association between adiponectin levels and newly diagnosed type 2 diabetes mellitus (T2DM) and pre-diabetes in subgroups classified according to T2DM risk factors. Setting: Sun Yat-sen Memorial Hospital of Sun Yat-sen University. Participants: 3680 individuals (1753 men and 1927 women) aged 18–70 years from Guangzhou and Dongguan, China, were enrolled from December 2018 to October 2019. Primary and secondary outcome measures: T2DM was defined as fasting plasma glucose (FPG)≥7.0 mmol/L or HbA1c≥6.5%, and pre-diabetes was defined as 6.1 mmol/L≤FPG<7.0 mmol/L or 5.7≤HbA1c<6.5%. Results: With the increasing number of T2DM risk factors, the proportion of the population with high-quartile adiponectin levels gradually decreased (p<0.001). A low level of adiponectin was significantly associated with diabetes and pre-diabetes in a population with ≥1 T2DM risk factor, whereas its association was not consistently significant in the population with all three T2DM risk factors. For instance, participants were more likely to have diabetes or prediabetes with low levels of adiponectin when they had ≥ one T2DM risk factor (quartile 2 vs. 1: OR 0.71 [95%CI: 0.56–0.89]; P=0.003; quartile 3 vs. 1: OR 0.57 [95%CIs: 0.44–0.72]; P<0.001; and quartile 4 vs. 1: OR 0.52 [95%CIs: 0.40–0.67]; P<0.001). Conclusion: Adiponectin was negatively associated with diabetes and pre-diabetes in a population with few T2DM risk factors, while their relationship gradually attenuated with the accumulation of T2DM risk factors, especially in a population with coexisting diseases such as obesity, hypertension and dyslipidaemia.